Changes in the Relationship Between the Long-Term Interest Rate and its Determinants - Lee, William (IMF Working Papers; Working Paper ;, 1994)
This paper assesses the relative importance of alternative explanations for the rise in long-term interest rates in the United States from October 1993 to April 1994. Standard econometric models of the term structure are shown to have a structural break in the early 1980s. An important reason for this change in the traditional term structure relationship appears to be an increase in the responsiveness of long-term rates to changes in the stance of monetary policy. Augmented term structure models that explicitly incorporate the role of monetary policy in determining the level of long-term rates are then constructed. These models track variations in the long-term rate better than traditional term structure models, but still leave a significant fraction of the recent increase in long-term rates unexplained.